STUDENTS’ PERCEPTIONS OF ICT INTEGRATION IN STEM AND HUMANITIES CLASSROOMS IN SECONDARY SCHOOLS - Tri Achmad Efendi; Amalia Silwana; Wisnu Kristianto; Alfina Citrasukmawati (LPPM Universitas Kahuripan Kediri, 2026)
This study examines students’ perceptions of ICT integration in STEM and Humanities areas. The researchers employed descriptive qualitative. Data were collected through an online questionnaire consisting of Likert-scale items and open-ended questions. A total of 139 secondary school students from several schools participated in the study. The findings revealed that students had positive perceptions towards ICT use in the teaching process. The findings also revealed that students perceived ICT to be used more frequently in STEM subjects than in Humanities disciplines, suggesting the presence of a potential subject-wise digital divide. Overall, the study concludes that while ICT integration is positively perceived by students, differences in its implementation across subject areas remain existed.